PREDICTING LISTENER’S MOOD BASED ON MUSIC GENRE: AN ADAPTED REPRODUCED MODEL OF RUSSELL AND THAYER - Worlu, Chijioke (Journal of Technology Management and Business, 2017)
Mood has presently received growing consideration as an interesting technique for organizing and accessing music. Stress which changes individual mood is a major physical and psychological problem of individuals today. Many researches have been conducted based on this study of mood, particularly in the U.S.A, Canada, Europe, and some part in Asia.Â However, while these studies are important, and help to solve the problem of mood change, still, researchers were unable to look into this important aspect in one of the 25 rapid growth markets in the world-Malaysia. In solving this problem, this study suggested using music genre as an influence mechanism to predict mood and again identify what kind of classified musical genre that can be used to predict certain mood. This study adapts and reproduces a model of Russell and Thayer to categorize moods. A total population of 245 university students of both sexes, aged from 18-56 and above, married and single, different educational level, race, and religions were used to achieved the objective of this study. The data was analyzed using SPSS version 20. The analysis results were presented based on majority and popularity of respondents. The findings indicate that the result of this study is 60%-80% percent positive on both part A and Part B due to the higher population respondents of the investigation. Hence, based on the findings, the study clearly interprets and presents an encouraging methodology that predicts the mood of the listener’s with a positive outcomes.